Comprehensive Molecular Detection of Tick-Borne Phleboviruses Leads to the Retrospective Identification of Taxonomically Unassigned Bunyaviruses and the Discovery of a Novel Member of the Genus Phlebovirus - Matsuno, Keita; Weisend, Carla; Kajihara, Masahiro; Matysiak, Colette; Williamson, Brandi N.; Simuunza, Martin; Mweene, Aaron S.; Takada, Ayato; Tesh, Robert B.; Ebihara, Hideki (Journal of virology, 2015)
Until the recent emergence of two human-pathogenic tick-borne phleboviruses (TBPVs) (severe fever with thrombocytopenia syndrome virus [SFTSV] and Heartland virus), TBPVs have been neglected as causative agents of human disease. In particular, no studies have addressed the global distribution of TBPVs, and consequently, our understanding of the mechanism(s) underlying their evolution and emergence remains poor. In order to provide a useful tool for the ecological and epidemiological study of TBPVs, we have established a simple system that can detect all known TBPVs, based on conventional reverse transcription-PCR (RT-PCR) with degenerate primer sets targeting conserved regions of the viral L genome segment. Using this system, we have determined that several viruses that had been isolated from ticks decades ago but had not been taxonomically identified are novel TBPVs. Full-genome sequencing of these viruses revealed a novel fourth TBPV cluster distinct from the three known TBPV clusters (i.e., the SFTS, Bhanja, and Uukuniemi groups) and from the mosquito/sandfly-borne phleboviruses. Furthermore, by using tick samples collected in Zambia, we confirmed that our system had enough sensitivity to detect a new TBPV in a single tick homogenate. This virus, tentatively designated Shibuyunji virus after the region of tick collection, grouped into a novel fourth TBPV cluster. These results indicate that our system can be used as a first-line screening approach for TBPVs and that this kind of work will undoubtedly lead to the discovery of additional novel tick viruses and will expand our knowledge of the evolution and epidemiology of TBPVs. IMPORTANCE Tick-borne phleboviruses (TBPVs) have been largely neglected until the recent emergence of two virulent viruses, severe fever with thrombocytopenia syndrome virus and Heartland virus. Little is known about the global distribution of TBPVs or how these viruses evolved and emerged. A major hurdle to study the distribution of TBPVs is the lack of tools to detect these genetically divergent phleboviruses. In order to address this issue, we have developed a simple, rapid, and cheap RT-PCR system that can detect all known TBPVs and which led to the identification of several novel phleboviruses from previously uncharacterized tick-associated virus isolates. Our system can detect virus in a single tick sample and novel TBPVs that are genetically distinct from any of the known TBPVs. These results indicate that our system will be a useful tool for the surveillance of TBPVs and will facilitate understanding of the ecology of TBPVs.